Catalogue of Lygistorrhinidae (Diptera: Bibionomorpha) types housed in the collection of the Museu de Zoologia da Universidade de São Paulo, Brazil - Oliveira, Sarah Siqueira; Falaschi, Rafaela Lopes; Lamas, Carlos José Einicker (Zootaxa, 2018)
This paper provides a catalogue of the type specimens of Lygistorrhinidae (Diptera: Bibionomorpha) held in the collection of the Museu de Zoologia da Universidade de São Paulo, Brazil (MZUSP). Label information and type condition of the six type specimens (three holotypes and three paratypes) of four species are provided, along with high resolution images of the types and their labels.